2008
DOI: 10.1097/nmd.0b013e318162a9e1
|View full text |Cite
|
Sign up to set email alerts
|

Deficits of Social-Cognitive and Social-Perceptual Aspects of Theory of Mind in Remitted Patients With Schizophrenia

Abstract: Although ToM deficit in schizophrenia is widely accepted, findings regarding remitted schizophrenia patients are contradictory. Because residual symptoms are present out of psychotic exacerbation periods, the differences between definition of remission may be important to interpret these findings. The purpose of this study was to investigate the relationship between performance of 2 different aspects of theory of mind (ToM) and residual clinical symptoms and other cognitive deficits in schizophrenia. Ninety-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 28 publications
4
59
0
3
Order By: Relevance
“…Both in patients and in individuals at genetic risk, mentalizing abilities seem to be related to and to interfere with the expression of psychotic symptoms or schizotypal traits [35][36][37]. Moreover, the relation of ToM and general cognitive function as well as the pattern of impairment of cognitive versus emotional ToM is still unclear [38].…”
Section: Introductionmentioning
confidence: 97%
“…Both in patients and in individuals at genetic risk, mentalizing abilities seem to be related to and to interfere with the expression of psychotic symptoms or schizotypal traits [35][36][37]. Moreover, the relation of ToM and general cognitive function as well as the pattern of impairment of cognitive versus emotional ToM is still unclear [38].…”
Section: Introductionmentioning
confidence: 97%
“…ToM dysfunction is widely recognized to be a key feature of schizophrenia [16] and autism [17], and it is also associated with other psychiatric disorders like bipolar disorder [18], anorexia nervosa [19], or borderline personality disorder (BPD) [20]. Some studies have demonstrated ToM impairment in remitted schizophrenia patients [21,22,23] and their first-degree relatives [22,24], suggesting that such dysfunction may represent a trait marker or endophenotype of the disorder [25]. ToM, which is one of the key aspects of social cognition, refers to the ability to judge one's own and other people's mental states, like their beliefs or intentions [26].…”
Section: Introductionmentioning
confidence: 99%
“…The participants are asked to select a word for each photo among four words. The test was translated into Turkish and used in studies with its shorter version (e.g., Bora, Gokcen, Kayahan & Veznedaroglu, 2008). In this study, some of Turkish translations of the items were reevaluated and replaced by more suitable Turkish words by two bilingual professionals from the psychology field.…”
Section: The "Reading the Mind In The Eyes" Test (Revised)mentioning
confidence: 99%